Analisis Pengaruh Nilai Impor, Nilai Tukar, dan Inflasi Terhadap Pertumbuhan Ekonomi Indonesia Tahun 2010-2021 - Herman Wily; Irsad Lubis (Universitas Batanghari, 2023)
The economic growth of every nation can be impacted by different factors. One of the indicators in measuring economic growth is by using the Gross Domestic Product (GDP). Because of this, the purpose of this study is to examine how variable import values, exchange rates, and inflation on Indonesia's economic growth for the period 2010 to 2021 with the GDP indicator. This quantitative study uses the Partial Adjustment Model (PAM) dynamic econometric model with secondary data obtained from the websites of the Badan Pusat Statistik (BPS) and World Bank. The results showed that the variable value of imports, exchange rates, and inflation positively affected economic growth. Exchange rate and inflation variables do not have a significant effect on economic growth in the short term but are significant in the long term, while the import value variable does not have a significant effect on economic growth in both the short and long term.